2018
DOI: 10.29252/jafm.11.03.27854
|View full text |Cite
|
Sign up to set email alerts
|

Ferrofluid Based Squeeze Film Lubrication between Rough Stepped Plates with Couple Stress Effect

Abstract: This investigation purposes to study the magnetic fluid based squeeze film behavior on transversely rough stepped plates with the influence of couple stress. Using the well-known stochastic model of Christensen and Tonder the roughness effect has been evaluated. The magnetic fluid flow model of Neuringer -Roseinweig has been adopted to obtain the influence of magnetization. The governing Reynolds' type equation is derived on the basis of stokes microcontinum theory for couple stress fluid. For the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The equation (17), equation (18) and equation ( 24) represent the closed form solution for pressure and load capacity. Equation (24) suggests that load capacity is enhanced by µ * (2K−1)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation (17), equation (18) and equation ( 24) represent the closed form solution for pressure and load capacity. Equation (24) suggests that load capacity is enhanced by µ * (2K−1)…”
Section: Resultsmentioning
confidence: 99%
“…Among all these models, the stochastic approach given by Christensen and Tonder [12][13][14] is used very widely. Many investigators have studied the combined influence of surface roughness and ferrofluid for a distinct porous bearing configuration [15][16][17][18][19][20]. All these scrutinies discovered that the load capacity of the bearing is improved due to ferrofluid and negatively skewed roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for industrial application, the study of lubrication with magnetic fluid is of primary importance. Some researchers (Deheri et al, 2016;Munshi et al, 2017;Patel et al, 2017;Vashi et al, 2018) have also used magnetic fluid as a lubricant in order to aid the tribological performance of a sliding interface. Christensen and Tonder (1969a, b;1971) used a stochastic concept and came up with a new model for lubricated surfaces with striated roughness using an averaging film.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the biggest inventions in the field is the use of ferrofluid as a bearing system lubricant. A number of authors [7][8][9][10][11] have worked to explain the performance and applications of ferrofluid when used in different types of bearing systems. These studies have suggested that ferrofluid impacts the bearing performance positively.…”
Section: Introductionmentioning
confidence: 99%